DNA gyrase stimulates transcription. - Akrigg, A; Cook, P (1980)
The nuclear DNA of HeLa cells can now be isolated unbroken and supercoiled. Using DNA gyrase and the untwisting enzyme, we have prepared an allomorphic series of templates derived from this nuclear DNA, and also from the circular DNA of the bacterial virus, PM2. We have then transcribed these templates using 2 different RNA polymerases--from wheat germ and Escherichia coli. Relaxed DNA is transcribed slowly by both polymerases. Supertwisting the naturally-supercoiled templates with gyrase slightly inhibits transcription by the bacterial polymerase but stimulates dramatically transcription by RNA polymerase II from wheat germ.